Álvaro T. Latorre - Influence Of Hyperelastic Properties On The Assessment Of Atherosclerotic Plaque Vulnerability By Inverse Analysis - Latorre, Alvaro (Jornada de Jóvenes Investigadores del I3A, 2023)
Alvaro T. Latorre